Problematika Awal Waktu Shubuh antara Fiqih dan Astronomi - Ardi, Unggul Suryo (Universitas Islam Negeri Mataram, 2020)
The issue of astronomical twilight as a sign of the time the early entry of the morning prayer, is inseparable from the problems between the perspective of fiqh and the perspective of astronomy. Astronomical twilight which is a benchmark as an early marker of Shubuh prayer, must be confronted with the dawn of the kazib which is a false twilight. This concern arises because if there is a slight mistake in distinguishing it, then it is not valid to pray a Muslim's body because it is not yet in time. On the other hand the relevance of the concept of the astronomical twilight in the perspectives of fiqh and astronomy sometimes clash. The result can cause confusion for ordinary people who do not understand that science. This is based on differences in the height of the sun. In its application, there are those who use the criteria -18o to -13o as the sun height value, but some use -19o and -20o. This is caused by several factors, namely natural factors, height of the place, weather conditions, air and light pollution, as well as factors that arise from the tool or the person observing it. Of the many factors, the greatest influence on differences in sun height criteria is the height of the place. Problematika fajar sebagai tanda waktu masuknya awal shalat Shubuh, tidak lepas dari persoalan antara prespektif fiqih dan prespektif astronomi. Fajar sadik yang merupakan patokan sebagai penanda awal waktu shalat subuh, harus dihadapkan dengan adanya fajar kazib yang merupakan fajar palsu. Kehawatiran ini muncul karena jika salah sedikit saja dalam membedakanya, maka tidak sah shalat shubuh seorang muslim karena belum masuk waktunya. Di sisi lain relevansi konsep fajar sadik dalam prespektif fiqih dan astronomi terkadang berbenturan. Akibatnya dapat menimbulkan kebingungan bagi masyarakat awam yang tidak memahami ilmu tersebut. Hal ini didasari karena adanya perbedaan terkait ketinggian matahari. Dalam penerapanya, ada yang menggunakan kriteria -18o sampai -13o sebagai nilai ketinggian Mataharinya, namun ada pula yang menggunakan -19o dan -20o. Hal ini di sebabkan oleh beberapa faktor yaitu faktor alam, tinggi tempat, kondisi cuaca, polusi udara dan cahaya, maupun faktor yang muncul dari alat maupun orang yang mengobservasinya. Dari sekian banyak faktor, yang paling besar pengaruhnya terhadap perbedaan kriteria ketinggian matahari ini adalah ketinggian tempat.